2002
DOI: 10.3354/meps241215
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of phototaxis and geotaxis during larval development of the sabellariid polychaete Phragmatopoma lapidosa

Abstract: Thorson generalized that the larvae of intertidal animals should remain photopositive throughout larval life to facilitate encounters with shallow surfaces at settlement. We tested this idea for the sabellariid polychaete Phragmatopoma lapidosa by investigating ontogenetic changes in phototaxis and geotaxis of well-fed, laboratory-reared larvae. Larvae at each of 5 age groups were exposed to (1) 8 different light intensities from a directional light source in a horizontal trough and (2) complete darkness in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…4d) in the sediment in May compared to April also point towards a release of organic matter from the ice into the water column and sediment at the end of May, similar to that reported by Horner and Schrader (1982). On the other hand, polychaete juveniles might have out-grown the brine channel diameters by late May (Krembs et al 2000), forcing them out of the sea ice, or they may have changed to negative phototaxis (McCarthy et al 2002). Although we did not measure the juvenile polychaetes, we observed that the majority were larger by late spring.…”
Section: Seasonal Development Of Ice Biota Through a Spring Bloom Cycsupporting
confidence: 73%
See 2 more Smart Citations
“…4d) in the sediment in May compared to April also point towards a release of organic matter from the ice into the water column and sediment at the end of May, similar to that reported by Horner and Schrader (1982). On the other hand, polychaete juveniles might have out-grown the brine channel diameters by late May (Krembs et al 2000), forcing them out of the sea ice, or they may have changed to negative phototaxis (McCarthy et al 2002). Although we did not measure the juvenile polychaetes, we observed that the majority were larger by late spring.…”
Section: Seasonal Development Of Ice Biota Through a Spring Bloom Cycsupporting
confidence: 73%
“…While counting the samples, we observed positive phototactic behavior of the polychaete juveniles, known from several polychaete species (e.g. McCarthy et al 2002). This provides a mechanism for moving from the plankton into the brighter sea ice, a change from a meroplanktonic life style to one we define analogously as merosympagic.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…There were clear ontogenetic changes in phototaxis observed in this study that were similar to those reported in other aquatic organisms such as mussels (Dobretsov & Miron 2001) and polychaetes (McCarthy et al 2002). The leptocephalus larvae lost their strong negative phototaxis during the advanced metamorphosing stage.…”
Section: Mechanism Of Diel Vertical Migrationsupporting
confidence: 70%
“…Despite the prevalence of positive phototaxis in larvae [1] and observations of positive phototaxis in younger oyster larvae [6], light had no observable effect on vertical swimming direction of our late-stage oyster larvae, suggesting an ontogenic shift in phototaxis. Ontogenic changes in phototaxis have been widely documented in larvae of eels [144], polychaetes [138,145], crabs [146], mussels [26], nudibranchs [147], conch [148], and both larval and juvenile sole [149]. Competent larvae may cease to display positive phototaxic behavior because they no longer need to stay afloat in the water column.…”
Section: Discussionmentioning
confidence: 99%